Diagnostic Capability of Pattern Electroretinogram and Three Circumpapillary Retinal Nerve Fiber Layer Thickness Circle Diameter Scans in Glaucoma Suspects - Tirsi A; Tsai J; Abizadeh A; Kacaj D; Procyk O; Gliagias V; Leung N; Yang H; Park SC; Tello C (Clinical Ophthalmology)
Andrew Tirsi,1,2 Joby Tsai,3 Aaron Abizadeh,2 Danielle Kacaj,4 Oksana Procyk,1 Vasiliki Gliagias,2 Nicholas Leung,2 Hanwen Yang,2 Sung Chul Park,1,2 Celso Tello1,2 1Department of Ophthalmology, Manhattan Eye, Ear, and Throat Hospital/Northwell Health, New York, NY, USA; 2Donald and Barbara Zucker School of Medicine at Hofstra/Northwell Health, Hempstead, NY, USA; 3Broward Health, Department of Ophthalmology, Fort Lauderdale, FL, USA; 4Cornell University, Ithaca, NY, USACorrespondence: Andrew Tirsi, Manhattan Eye Ear & Throat Hospital/Northwell Health, Department of Ophthalmology, 210 East 64th Street, New York, NY, 10065, USA, Tel +1 201 982 4168 ; +1 646 785 8217, Email atirsi@northwell.eduPurpose: To assess the diagnostic capability of pattern electroretinography (PERG) and varying circumpapillary optical coherence tomography (OCT) scan diameters in glaucoma suspects (GS).Methods: This is a prospective, cross-sectional study. Circumpapillary retinal nerve fiber layer thickness (RNFLT) was measured using spectral domain OCT in 49 eyes from 26 patients (36 normal, 13 GS) in three circle diameters (3.5, 4.1, and 4.7 mm). PERG measurements (Magnitude [Mag], MagnitudeD [MagD], MagnitudeD/Magnitude [MagD/Mag] ratio) were used. Based on clinical examination, participants were classified as controls or GS. Independent t-test and areas under the receiver operating characteristic curve (AUC) were obtained to determine the diagnostic capability of PERG and OCT.Results: Independent t-test revealed significant differences between controls and GS in age, sex, central corneal thickness (CCT), all PERG parameters, and global RNFLT (gRNFLT) in three circle diameters. All PERG parameters were correlated to all RNFLT sectors (r > 0.291; p < 0.041), except in the temporal and nasal sectors of the three circle scans. Spearman rho was highest in 3.5 and lowest in 4.7 mm circle scan. AUC demonstrated 3.5 mm gRNFLT had the highest diagnostic capability (AUC = 0.877), followed by 4.1 mm gRNFLT (AUC = 0.852), and 4.7 mm gRNFLT (AUC = 0.821). MagD showed the foremost diagnostic capability (AUC = 0.81), followed by Mag (AUC = 0.799) and MagD/Mag (AUC = 0.762).Conclusion: Global, superior, and inferior RNFLT in 3.5 and 4.1 mm diameters, and MagD performed best in discriminating GS from controls, suggesting that a larger scan of 4.1 mm may be equally useful in glaucoma diagnosis as the conventional 3.5 mm diameter. We recommend using PERG with OCT of 3.5 or 4.1 mm diameters for glaucoma suspect diagnosis.Keywords: glaucoma suspects, glaucoma, PERG, SD-OCT, RNFL